Array-based digital sun-sensor design for CubeSat application. (January 2021) - Bolshakov, Konstantin; Diriker, Fuat Kaan; Clark, Ryan; Lee, Regina; Podmore, Hugh
Abstract: A Custom-designed, digital sun sensor based on the orthogonal photodiode array is proposed. A well-known application of geometrical aperture mask on light detectors is utilized in a non-conventional design for CubeSat application. The main characteristic of this design is the inclusion of a chirped pattern of slits, while using a digital readout of the photodiode arrays. This pattern is expected to allow greater angle detection accuracy while digital photodiode readout decreases complexity and power consumption. The array-based design approach features low power requirements and simpler readout interface and signal processing when compared to matrix-based approach. The proposed sun sensor design will be demonstrated on DESCENT CubeSat as a part of the technology demonstration payload. The characterization of the prototype sensor shows that the current 5-slit design achieves 0.3-degree accuracy with ±51.5-degree field-of-view (FOV). Highlights: Five categories of sun sensor designs are described based on the sensing method. Linear array design with digital read-out circuit is proposed as CubeSat attitude sensor. The proposed sensor features 103-degree field-of-view with the dimension of 11 × 11 × 3 mm enclosure. Simulation and in-lab characterization predict 0.3-degree mean error accuracy.